Between pain and hope: Examining women's marginality in the evangelical context. Issue 4 (November 2019) - Gaddini, Katie Christine
This article examines religious and gendered identities through an ethnographic study of unmarried evangelical Christian women in London. Moving away from an approach that shows that women feel empowered through their conservative, male-dominated religious environment, or else they find it constraining and leave the church, this article investigates the experiences of women who feel limited by their church, and still remain embedded in their Christian environment. The article begins by exploring the normative figure of the ideal Christian woman operative in this context. It then describes the experiences of women who do not fit the norm, outlining the affective toll they suffer through marginality. Finally, the article examines how some women rely on hope in order to change the normative framework within their church. This article argues that leaving and staying are not static categories; instead evangelical women, frustrated with their marginal positions, revealed a continuum of investment underlain by resilience and hope.